(untitled) (Diametros, 2010)
Rather than to focus upon a particular ‘right to life’, we should consider what rights there are pertaining to our lives and to our living. There are different sorts. There are, for instance, rights that constitute absences of particular duties and rights that correspond to the duties of other agents or agencies. There are also natural and non-natural rights and duties. Different people in different contexts can have different moral duties and different moral rights including rights to life. The question of the moral rights there are to and pertaining to life is considered with reference to James Griffin’s account of human rights. Also considered is the question of who or what can be a bearer of them.